An Analysis of the Quality Test Items Used in the Final Semester Assessment at MTs Nurul Yaqin Gili Air - Memy Wardani Elthia; Rosidah Alawiyah (Departement of Mathematics Education, 2023)
The objective of this study is to provide a comprehensive analysis of the item test quality for English final semester exams presented to ninth-grade students during the academic year 2022/2023 at Mts Nurul Yaqin. This study aims to offer feedback and serve as a model for English teachers, educators, test developers, and other individuals involved in the creation of English tests. The analysis will focus on evaluating item difficulty, item discrimination, and the efficacy of distractors. The results of the research show that the final semester exam question quality is very good, since most of the questions in level of difficulty fall within the medium questions. In index of distinguishing power is also good, due to the fact that the highest percentage of questions is in the category of good questions. Then, in terms of the distractor function, based on the results of students' answers, it is categorized as having a distractor that has been functioning properly.